Estudio de adaptación de siete Pastos y Tres mezclas Forrajeras con la utilización de Lactofermento en el Barrio San Luis de Yacupungo Parroquia Pastocalle Cantón Latacunga Provincia de Cotopaxi, 2018. - Sambache Tayupanta, José Rafael (2018)
This investigation was carried out in San Luis de Yacupungo Neighborhood, Pastocalle Parish, Latacunga Canton, Cotopaxi Province, at an altitude of 3250 meters above sea level and coordinates 07669966 and 9923785, with the objective of studying the adaptation of seven pastures and three forage mixtures with the use of lactoferment. A design of divided plots, 20 treatments, and three repetitions were applied, giving a total of 60 experimental units. The methodology to be followed was perform a soil analysis to determine the number of nutrients, delimit the land and install the plots for each treatment, the sowing was done by hand and according to the sketch of the trial, the preparation of lactoferment was carried out in a 200-liter tank, using bovine manure, water, molasses, whey, phosphate rock, coal ash and sulfates of zinc, magnesium, manganese, ferrous and potassium. The data was taken at eight days for seed germination in the field and the determination of its percentage; while for the height, it was at 58, 72 and 86 days; the coverage was at 87 days and the parameters of the analysis bromatological after obtaining the results. The research expressed the following results: the highest average percentage of germination was for P5 (Chicory) with 97.5%; in the interaction Oat grass with lactoferments (P7L1) reached high standards for the variable height of plants at 72 days with 45.9 and at 86 days with 54.2. For the interaction in coverage P4L1 (Rye Grass with lactoferment). For the results of the bromatological analysis the highest average in protein was for P3 (white clover) that got an average of 20.36% P4 (Rye Grass) that obtained an average of 27.55% in the amount of crude fiber. The best standards by location were obtained by humidity (82.69), protein (18.2) and fat (2.47) in San Luis. In the economic analysis, the lowest cost represented T2 (red clover), with only 50 USD / ha, while T9 (Vicia Sativa + Oats) is the least expensive forage mix with a value of 175 USD / ha.